Heat Transfer in Single-side Napped Fabrics During Compression (Journal of Fiber Bioengineering and Informatics, 2014)
This paper presents a systematic analysis of the changes in thickness and the differences in the heat fluxtransfer for the two surfaces of selected single-side napped fabric, to explore the relationship betweentheir heat flux and thickness during compression. The results showed that heat flow in the un-nappedsurface was greater than that in the napped surface when the fabric initially contacted the upper plate ofa Fabric Touch Tester (p ‹ 0.05); few differences of the heat flux between the un-napped and the nappedsurfaces measured separately with each surface facing upwards for each fabric type were observed whenthe pressure exceeded 0.6 Pa (p › 0.05); the heat flux was linearly correlated with thickness for both theun-napped surface and napped surface when the pressure exceeded 0.6 Pa (correlation coefficient R² ›0.9); the gradients of the regression equation of heat flux-thickness gradually increased from the initialthickness point to the midpoint of the maximum pressure except for the first heat peak point of theun-napped surface. In conclusion, heat flux was significantly affected by the surface characteristics ofthe fabrics in the initial stages of compression but was then not affected by either the surface features orthe fabric structures at higher levels of compression pressure. The conclusion could be useful in productdevelopment and in providing a guide for clothing wearing comfort.